"Anything that Causes Chaos": The Organizational Behavior of Russia Today (RT). (28th September 2020) - Elswah, Mona; Howard, Philip N
Abstract: RT (formerly, Russia Today) is one of the most important organizations in the global political economy of disinformation. It is the most richly funded, well-staffed, formal organization in the world producing, disseminating, and marketing news in the service of the Kremlin. It is an agency accused of many things, but little is known about all the creative work involved in financing, governing, training, and motivating RT's activities. To understand more about the production of political news and information by RT, we investigate its organizational behavior through in-depth interviews of current and former staff. Our data show that RT is an opportunist channel that is used as an instrument of state defense policy to meddle in the politics of other states. The channel has been established in the shadows of the Soviet media system and its organizational behavior is characterized by Soviet-style controls.